2019
DOI: 10.20870/oeno-one.2019.53.3.2460
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the anthocyanins composition of five wine-making grape cultivars cultivated in the Wujiaqu area of Xinjiang, China

Abstract: Anthocyanins biosynthesis are essentially determined by grape cultivar genotype. However, specific environmental and vine management conditions could alter the accumulation of anthocyanins. This study selected five wine-making grape cultivars cultivated in the Wujiaqu area of the Xinjiang region of China to investigate the profiles of anthocyanins. Results showed that a total of 15 anthocyanins were identified. Marselan contained 15 anthocyanins, whereas only 14 anthocyanins were present in Cabernet-Sauvignon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Similarly, in some hot regions with higher temperature, grape phenological timing is accordingly advanced, which leads to a change of growing season in the time period (Jarvis et al, 2017). For example, in Xinjiang, Cabernet Sauvignon fully ripens in the middle of August (Zhang et al, 2019), thus the calculation of accumulated temperature from April to September may show an overestimation. Rather than a fixed time period, the climate conditions should be evaluated regularly, especially for some key pheno-phases.…”
Section: Limitations and Expectationsmentioning
confidence: 99%
“…Similarly, in some hot regions with higher temperature, grape phenological timing is accordingly advanced, which leads to a change of growing season in the time period (Jarvis et al, 2017). For example, in Xinjiang, Cabernet Sauvignon fully ripens in the middle of August (Zhang et al, 2019), thus the calculation of accumulated temperature from April to September may show an overestimation. Rather than a fixed time period, the climate conditions should be evaluated regularly, especially for some key pheno-phases.…”
Section: Limitations and Expectationsmentioning
confidence: 99%
“…The mass concentration of phenolic and coloring substances in the clones of Cabernet-Sauvignon, Merlot and Bastardo Magarachsky exceeded those of traditional varieties. In general, the value of these indicators of all studied wine materials corresponded to the values typical for the Western European ecological-geographical group [5][6][7][8][9][10][11][12][13][14][15]. Tasting assessments of the studied wine materials are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 58%
“…As regards acetates, the percentages shown by the hybrids were much higher than that seen in Monastrell, which had an average during the 3 years of 3% compared with the 26% for MC4, (close to that of Cabernet Sauvignon variety) and 14% for MS34. Zhang et al (37) reported that Cabernet-Sauvignon and Syrah exhibited a high level of acetylated and coumarylated anthocyanins, respectively, so it is possible that the most of our crosses have a pattern of acylation closer to Cabernet Sauvignon or Syrah varieties.…”
Section: Profile Of Anthocyanins In Grapesmentioning
confidence: 93%